2015
DOI: 10.1007/s00345-015-1666-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the first and repeated intradetrusor injections of abobotulinum toxin A 750 U for treating neurological detrusor overactivity

Abstract: The results of the present study are in favor of a long-term safety and efficacy of abobotulinum toxin A 750 U for NDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In a retrospective study with a mixed group of neurological patients with refractory LUT dysfunction using intradetrusor injections of 750 IU abobotulinumtoxinA, 64% of patients reported significantly improved continence rates after 6 weeks and a reduction in mean maximum detrusor pressures comparable to after onabotulinumtoxinA use. The study confirmed long-time safety and efficacy of abobotulinumtoxinA 750 IU over a mean follow-up of 28 months [ 71 ••].…”
Section: Intravesical Treatmentssupporting
confidence: 56%
“…In a retrospective study with a mixed group of neurological patients with refractory LUT dysfunction using intradetrusor injections of 750 IU abobotulinumtoxinA, 64% of patients reported significantly improved continence rates after 6 weeks and a reduction in mean maximum detrusor pressures comparable to after onabotulinumtoxinA use. The study confirmed long-time safety and efficacy of abobotulinumtoxinA 750 IU over a mean follow-up of 28 months [ 71 ••].…”
Section: Intravesical Treatmentssupporting
confidence: 56%
“…According to their study, after treatment 19 patients had a significant decrease in mean maximum detrusor voiding pressure at 36 weeks follow-up. Furthermore, over the past 15 years there has been rapid progress in research into the clinical and urodynamic benefits of BTX-A for NDO secondary to SCI (21). Although the follow-up period was relatively short, our trial also reported an mean reduction of 28.78 cm H 2 O in maximum detrusor pressure (P detmaxDO-DESD ) and a mean increase of 54.56 ml in V DO-DESD .…”
Section: Discussionmentioning
confidence: 76%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] The level of evidence of the included studies ranged from 3 to 4. Ten studies were retrospective case series, [12][13][14][15][16][17][18][19]22,27 seven studies were prospective cohort studies 11,20,21,23,24,26,28 and the remaining article was a mixed study comprising both retrospective and prospective components. 25 Thirteen studies used Botox, 12,15,[17][18][19][20][21][23][24][25][26][27][28] four studies used Dysport, …”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Ten studies were retrospective case series, [12][13][14][15][16][17][18][19]22,27 seven studies were prospective cohort studies 11,20,21,23,24,26,28 and the remaining article was a mixed study comprising both retrospective and prospective components. 25 Thirteen studies used Botox, 12,15,[17][18][19][20][21][23][24][25][26][27][28] four studies used Dysport, 13,14,16,22 and one study used both Botox and Dysport. 11 Botox was administered at doses of 200 or 300 U, and Dysport was administered at doses ranging from 500 to 1000 U.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation